Contagious Bovine Pleuropneumonia: Seroprevalence and Risk Factors in Gimbo District, Southwest Ethiopia. (24th May 2018) - Mamo, Yosef; Bitew, Molalegne; Teklemariam, Tsegaye; Soma, Murga; Gebre, Debebe; Abera, Temesgen; Benti, Tefera; Deneke, Yosef
Abstract : Contagious bovine pleuropneumonia (CBPP) is a highly contagious disease of cattle which is one of the great plagues which continues to devastate the cattle herds on which so many people are dependent in Africa. Cross-sectional study was conducted from October 2015 to August 2016 to determine the seroprevalence of CBPP in cattle and associated risk factors in Gimbo district, Southwest Ethiopia. A total of 384 serum samples were collected and tested for the presence of specific antibodies against Mycoplasma mycoides subspecies mycoides small colony (MmmSC), using a competitive enzyme-linked immunosorbent assay (cELISA). Univariable and multivariable logistic regression analysis were performed to determine the association between risk factors and seroprevalence of CBPP. An overall seroprevalence of CBPP was 8.1% (31/384) and it was ranging from 0% to 20% across different Peasant associations (PAs). The seroprevalence of CBPP among adult animals was 8.5% (25) and in young 6.6% (6), in good body condition animals 6.6% (18) and in poor 11.5% (13), in dry season 11.9% (20) and in rainy 5.1% (11), and in highland altitude 2.5% (3), midland 3.8% (5), and lowland 17.4% (23). Among the potential predisposing factors assessed, altitude was found significantly (p = 0.02, OR = 7.3) associated with the seroprevalence of contagious bovine pleuropneumonia and other risk factors had no significant (P > 0.05) influence. The present study showed that the overall seroprevalence of CBPP in Gimbo district was high and this indicates a need for intervening and implementing control measures to prevent further spread of the disease in the district through the use of better and coordinated vaccination program.